Pengembangan Sistem E-learning Berbasis Web Pada Sekolah Tingi Teknologi Informatika Sony Sugema - Alif Nur Faturrobani; Gilang Cahyadi; Mahpudin (Program Studi Teknik Informatika Universitas Nusa Putra, 2024)
Sony Sugema College of Information Technology is one of the educational institutions that has a data processing system, so it requires that all data can be processed properly, stored in an orderly manner and its origin can be easily traced. However, the academic system used still has shortcomings, namely not optimal course participation, management of student data, teacher data, course schedules, course allocation and the absence of an online learning system throughout the semester. Then, to overcome deficiencies in the academic system, the author aims to develop the academic system of the Sony Sugema College of Information Technology using the Waterfall software development method. Then develop a system using the Hypertext Preprocessor (PHP) programming language, MySQL database and bootstrap framework, as well as Visual Studio Code as a coding tool. By creating this information system, it is hoped that it can help schools in managing learning data. The final result of this research is a web-based E-learning system that can optimize attendance information services, manage student data, lecturer data, lecture schedules, course classification, course division, and online learning systems during the semester period.